Nasal lobular capillary hemangioma: etiologic factors - Lemos, Ricardo Costa S.; Fonseca, Rui (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Nasal lobular capillary hemangioma (LCH) is a rare and benign vascular tumor of unknown etiology, often associated with hormonal factors and a history of trauma. In this case series we present twelve cases of nasal LCH diagnosed on patients treated at the Hospital da Senhora da Oliveira from January 2010 and December 2019. Of the 12 patients, 66, 7% were males. The most common clinical presentation was epistaxis (75%) followed by nasal obstruction (50%). In 75% of patients the most commonly affected area was the nasal septum. Regarding proposed contributing factors, nasal trauma was the most prevalent (33%), followed by the use of oral contraceptives (25%) and pregnancy (8.3%). Endoscopic sinus surgery was performed in all patients, with complete excision of the lesion, and no post-operative complications were observed. Nasal LCH should be considered in the differential diagnosis of nasal vascular lesions associated with unilateral epistaxis and nasal obstruction. Complete surgical resection should be the treatment of choice, since it’s associated with lower risk of recurrence.